Understanding the orientation of water molecules around the phosphate and attached functional groups in a phospholipid molecule: a DFT-based study - Mishra, Deepti; Das, Susanta; Krishnamurthy, Sailaja; Pal, Sourav (Molecular Simulation, 2013)
The adsorption of water molecules around a polar region (in particular around the phosphate moiety) in the phospholipid molecules is studied in this work. Phospholipid molecules with different functional groups are known to respond differently to the water molecules. Hence, we attempt to study the adsorption of water molecules around the phosphate group as a consequence of the change of functional group attached to the phosphate group, viz. phosphatidyl ethanolamine (PE), phosphatidyl choline (PC) and phosphatidyl glycerol (PG). As the latter is anionic in nature, the charge is compensated by Na+ counterion. Up to seven water molecules are adsorbed around the phosphate groups in model systems mimicking phospholipid molecule. The corresponding changes in the structural and electronic aspects are analysed. The significant difference between the PE and PC model systems is the formation of clathrate-like structure in the latter. Itisnoticed that as the number of water molecules increases to seven, both the hydrogen atoms in the water molecule participate in hydrogen bonding. However, in the PG model system, the charge-compensating counterion prevents the water molecule to form clathrate-like structures. The adsorption sites for water molecules are validated by density functional theory-based reactivity descriptors, viz. Fukui functions in the PE model system.
Keywords: cHelpG; DMPC; DMPE; DMPG; Fukui functions; Hydration